How did I remember to do that? Self-reported strategy use for laboratory prospective memory tasks. Issue 9 (21st October 2019) - Reese-Melancon, Celinda; Harrington, Erin E.; Kytola, Keri L.
ABSTRACT: The role of metacognition in prospective memory (PM) has received relatively little attention. This study combined data from several experiments to identify the strategy repertoire employed during a classic laboratory PM task and to determine whether self-reported strategy was related to performance. Participants ( N = 668) completed either a focal or nonfocal PM task embedded in an ongoing lexical decision task. The results indicated that participants reported the same strategy repertoire regardless of PM task focality. Participants who reported using a strategy performed better than those who did not report using one, and this was especially true under nonfocal conditions. Self-reported strategy use was also associated with more cost to the ongoing task when the opportunity to complete the PM task was present. These findings add to what is known about the metacognitive components of PM and underscore the need for additional research in this area.